First Multy-Proxy Studies Of High-Mountain Lakes In Armenia: Preliminary Results - Tatyana V. Sapelko; Vladimir R. Boynagryan; Mikhail A. Naumenko; Dmitry V. Sevastyanov; Ivan G. Gabrielyan; Artak S. Piloyan; Liana A. Margaryan; Mikhail Yu. Aleksandrin; Anton V. Terekhov (Geography, Environment, Sustainability, 2019)
Within the framework of the Russian-Armenian project “The Paleolimnological Aspect of Studying the Evolution of Ecosystems of High-Mountain Lakes of Russia and Armenia” in July-August 2018, we investigated four high-mountain lakes of Armenia. The research focuses on the lakes Kari, Umroi, Akna and Sev. All investigated lakes are located at the altitudes about 3000 m above sea level. We first time these lakes were investigated using a multi-proxy method that includes paleolimnological, geomorphological, hydrological, geochemical and biogeographic studies. The research offers the first statistical characteristics of lake depth distribution, water volume and other morphometrics. Lake sediments sequences and radiocarbon dates were received and analyzed for Armenian small lakes for the first time. We determined that all the studied lakes were formed during the Holocene. Sediments of Lake Kari were deposited in the last 4000 years, sediments of Lake Umroi – within the last 8000 years, while maximum thickness of sediments is around 1 m in both lakes. Hence, we assume low deposition rate in Armenian high-mountain lakes, however, it varied significantly in different periods of lake history.